Evolution of the rostral scale and mimicry in the genus Xenodon Boie, 1826 (Serpentes: Dipsadidae: Xenodontinae) - Cabral, Hugo [UNESP]; Cacciali, Pier; Santana, Diego Jose (Oxford Univ Press, 2022)
Snakes are a stimulating life form from an evolutionary perspective. Despite the basic morphological body shape (limbless, with a tubular body), these vertebrates are extremely diverse. The Neotropical region is one of the most diverse regions for snakes in the world, with >650 known species. Within this great diversity, the genus Xenodon includes 12 species with interesting adaptations to terrestrial and semi-fossorial habitats. Members of this genus are mostly diurnal and terrestrial, feed mainly on anurans and exhibit Batesian mimicry of venomous snakes of the genera Bothrops or Micrurus. Here, through phylogenetic analysis and ancestral state estimation, we explore the evolution of the rostral scale and mimicry within the genus Xenodon. Our results suggest that the ancestral lineage of Xenodon had a rounded rostral scale and exhibited Bothrops mimicry. The evolution of the rostral scale in Xenodon might be related to abiotic factors, as an adaptation for open and forested habitats, and mimicry is likely to be related to biotic factors, as a defensive strategy resembling those of venomous snakes.
Keywords: Batesian mimicry; Bothrops; Forest habitats; Micrurus; Neotropics; Open areas; South America; Snakes